2009
DOI: 10.1093/nar/gkp292
|View full text |Cite
|
Sign up to set email alerts
|

DIANA-microT web server: elucidating microRNA functions through target prediction

Abstract: Computational microRNA (miRNA) target prediction is one of the key means for deciphering the role of miRNAs in development and disease. Here, we present the DIANA-microT web server as the user interface to the DIANA-microT 3.0 miRNA target prediction algorithm. The web server provides extensive information for predicted miRNA:target gene interactions with a user-friendly interface, providing extensive connectivity to online biological resources. Target gene and miRNA functions may be elucidated through automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
391
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(398 citation statements)
references
References 14 publications
(17 reference statements)
0
391
0
7
Order By: Relevance
“…S1C). miR-23a and miR-23b share most, if not all, predicted target genes by TargetScan and DIANA Lab, as do miR-27a and miR-27b (19,20).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…S1C). miR-23a and miR-23b share most, if not all, predicted target genes by TargetScan and DIANA Lab, as do miR-27a and miR-27b (19,20).…”
Section: Resultsmentioning
confidence: 95%
“…S1C). miR-23a and miR-23b share most, if not all, predicted target genes by TargetScan and DIANA Lab, as do miR-27a and miR-27b (19,20).Northern-blot analyses revealed that miR-23a/b, miR-27a/b, and miR-24 are expressed at the highest levels in the lung and heart, which are highly vascularized tissues (Fig. 1B).…”
mentioning
confidence: 93%
“…42 In addition, mRNAs predicted by both the miRWalk and DIANA-microT algorithms to be targets of the 28 altered miRNAs were downloaded from the miRWalk database. 42,45 Pathway analysis was performed on the validated mRNA targets using IPA ® (Ingenuity ® Systems), and the validated and predicted data sets were mined for mRNAs known to be involved in epigenetic modification. 43,44 Real-time PCR.…”
Section: Methodsmentioning
confidence: 99%
“…components of the epigenetic machinery. We mined our validated data set, plus a predicted data set (targets predicted by miRWalk and DIANA-microT), 42,45 for mRNAs known to be involved in DNA methylation or histone modification. In total, 25 components of the epigenetic machinery were shown to be targets of the altered miRNAs [78 interactions: 5 validated and 73 predicted, respectively ( Table 2)].…”
mentioning
confidence: 99%
“…To investigate the mechanism through which miR-135a induced apoptosis of malignant glioma, we searched putative target genes by using TargetScan (Lewis et al, 2005) and DIANA-microT (Maragkakis et al, 2009) algorithms, and suggested that STAT6 and SMAD5 may associate with apoptosis (Sun et al, 2005;Zhang et al, 2008). We firstly transfected miR-135a and examined the protein levels of STAT6 and SMAD5 by western blotting.…”
Section: Mir-135a Targets Genes Associated With Mitochondrial Apoptotmentioning
confidence: 99%